La sociologia della crisi in Alain Touraine - Villa, Andrea (SocietàMutamentoPolitica, 2011)
From the sociological point of view, not only, the economic crisis is the cause of painful changes for people, but also, it represents the effect of a wider political and social crisis. With this assumption, Alain Touraine tries to look after the economic crisis and, through a situation that he calls «post-social», he tries to observe new actors and a possible innovation of social and political institutions. The paper explores some essential features of this original analysis, highlighting the main theoretical tools.